Development and validation of the social media perception scale for preservice physical education teachers - Xu, Yue; Li, Fangfei; Yin, Zhihua; Sun, Mingzhu; Guo, Zhen; Liu, Bo (Frontiers in Psychology, 2023)
Background Social media has become a mainstay of preservice physical education teachers’ professional development. However, previous studies have been dominated by qualitative research, and there is still a lack of quantitative research based on samples from eastern countries. The objective of this study is to develop and validate of the Social Media Perception Scale for Preservice Physical Education teachers (SMPS-PPE). Method Items of questionnaire created from 70 concepts of the perception model described in our previous study. Questionnaire survey was used to collect quantitative data from a sample of 977 preservice physical education teachers through surveys. We analyzed the data using SPSS 26.0 and AMOS 24.0, conducting item analysis, exploratory factor analysis and confirmatory factor analysis to examine the data. Results SMPS-PPE consists of 26 items grouped into three factors: value perception, risk perception, and overall perception. Our findings indicate that SMPS-PPE has acceptable content validity, internal structure validity, and internal consistency. Conclusion SMPS-PPE is a reliable and valid measurement to evaluate social media perception among preservice physical education teachers. Future studies should include larger and more diverse teacher samples to enhance generalizability. The SMPS-PPE should also be modified to better cater to the specific requirements of school teachers and university-based teacher educators in the field of physical education.